Working Paper 13: Collective Action and corruption - Pieth, Mark (Basel Institute on Governance Working Papers, 2012)
The working paper outlines the historical background and early experiments in the field of Collective Action. It also examines methods and challenges and depicts recent examples of Collective Action initiatives.